Efektifitas Media Pembelajaran PPT Canva terhadap Peningkatan Hasil Belajar Mata Pelajaran Fiqih di Kelas X MA Islamic Centre Bin Baz Yogyakarta Tahun Ajaran 2024/2025 - Muthmainnah Jannati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Fiqh learning at MA Islamic Centre Bin Baz Yogyakarta faces challenges, particularly in understanding the Fathul Qarib Al-Mujib book, which is written in Arabic. This difficulty is more pronounced among students without a pesantren background, affecting their academic performance. Observations indicate that only 60% of students achieve learning mastery, while 40% score below the minimum competency standard (KKM) of 80. To address this issue, this study aims to examine the effectiveness of PPT Canva as a learning medium in improving the learning outcomes of tenth-grade students. This research employs a quasi-experimental method with a Nonequivalent Control Group Design. The sample consists of two classes: the experimental class, which uses PPT Canva, and the control class, which does not. Data were collected through written tests (pretest and posttest), observations, and documentation, then analyzed using the t-test and N-Gain test with SPSS Windows 25. The findings reveal that using PPT Canva significantly improves learning outcomes, with a significance level of 0.032 (<0.05). The average pretest score for the experimental class was 54.14, increasing to 84.34 in the posttest, with an N-Gain score of 0.6469 (moderate category). The percentage of learning mastery increased from 0% to 85.71%. Thus, it can be concluded that using PPT Canva is effective in enhancing Fiqh learning outcomes for tenth-grade students at MA Islamic Centre Bin Baz Yogyakarta.